2019
DOI: 10.5539/jas.v11n2p465
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Basal Temperature and Its Relationship With Jatropha Crop in Irrigated and Non-irrigated System

Abstract: Full plant growth and development require, among others, air temperatures and water availability at levels appropriate to each crop. The effect of temperature on plant development can be represented by the thermal sum, which requires the lower basal temperature for each plant species. However, plant responses may be different when associated with different soil water contents. This work determined the lower and upper basal temperature of Jatropha curcas L. and verified the relationship between thermal sum and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
0
0
2
Order By: Relevance
“…Temperaturas basais superiores têm sido determinadas para espécies, tais como: 30ºC, 34ºC, 34ºC e 28ºC, nas fases poda-brotação, brotação-florescimento, florescimentofrutificação e maturação, respectivamente, para nectarina e pêssego (SOUZA; LEONEL; SILVA, 2011); 32ºC para mangueira (RODRIGUES; SOUZA; LIMA, 2013); 38ºC para feijão-caupi (FARIAS et al, 2015); e 38,8ºC e 36,8ºC, respectivamente, para os estágios de maturidade e ciclo total de pinhão-manso (Jatropha curcas L.) (MORAES et al, 2019).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Temperaturas basais superiores têm sido determinadas para espécies, tais como: 30ºC, 34ºC, 34ºC e 28ºC, nas fases poda-brotação, brotação-florescimento, florescimentofrutificação e maturação, respectivamente, para nectarina e pêssego (SOUZA; LEONEL; SILVA, 2011); 32ºC para mangueira (RODRIGUES; SOUZA; LIMA, 2013); 38ºC para feijão-caupi (FARIAS et al, 2015); e 38,8ºC e 36,8ºC, respectivamente, para os estágios de maturidade e ciclo total de pinhão-manso (Jatropha curcas L.) (MORAES et al, 2019).…”
Section: Resultsunclassified
“…Farias et al (2015) determinaram que as temperaturas basais inferior e superior de feijão-caupi, cultivar BR3 Tracuateua, são 8,55ºC e 38ºC, respectivamente. Foram determinadas temperaturas basais inferior de 4,9ºC e 7,2ºC e superior de 38,8ºC e 36,8ºC, respectivamente, para os estágios de maturidade e ciclo total de pinhão-manso (Jatropha curcas L.) (MORAES et al, 2019).…”
Section: Introductionunclassified
“…The thermal requirements for the formation of the first fruit cluster were 1982˚D accumulated. Moraes et al [29] evaluated Jatropha curcas irrigated and non irrigated systems, they found for fruit development was required 3271˚D and 2245˚D, respectively. In more favorable environmental conditions, the plants require more degree days for flowering, whereas a higher percentage of energy is expended on growth and dry matter accumulation.…”
Section: Phenology Of Jatropha Platyphyllamentioning
confidence: 99%